High hydrostatic pressure harnesses the biosynthesis of secondary metabolites via the regulation of polyketide synthesis genes of hadal sediment-derived fungi - Deng, Ludan; Zhong, Maosheng; Li, Yongqi; Hu, Guangzhao; Zhang, Changhao; Peng, Qingqing; Zhang, Zhizhen; Fang, Jiasong; Yu, Xi (Frontiers in Microbiology, 2023)
Deep-sea fungi have evolved extreme environment adaptation, and possess the huge biosynthetic potential of bioactive compounds. However, not much is known about the biosynthesis and regulation of secondary metabolites of deep-sea fungi under the extreme environments. Here, we presented the isolation of 15 individual fungal strains from the sediments of the Mariana Trench, which were identified by internal transcribed spacer (ITS) sequence analysis as belonging to 7 different fungal species. High hydrostatic pressure (HHP) assays were performed to identify the piezotolerance of the hadal fungi. Among these fungi, Aspergillus sydowii SYX6 was selected as the representative due to the excellent tolerance of HHP and biosynthetic potential of antimicrobial compounds. Vegetative growth and sporulation of A. sydowii SYX6 were affected by HHP. Natural product analysis with different pressure conditions was also performed. Based on bioactivity-guided fractionation, diorcinol was purified and characterized as the bioactive compound, showing the significant antibacterial and antitumor activity. The core functional gene associated with biosynthetic gene cluster of diorcinol was identified in A. sydowii SYX6, named as AspksD. The expression of AspksD was apparently regulated by the HHP treatment, correlated with the regulation of diorcinol production. The results showed that the HHP of the Mariana Trench affected the fungal development and secondary metabolites, as well as the expression level of biosynthetic genes which revealed the adaptive relationship between the metabolic pathway and the high-pressure environment at the molecular level.